Penerapan Healing Garden pada Rumah Sakit Jantung Aceh dengan Konsep Vertikal - Muhammad Irshad Ma’ruf (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2020)
This paper describe the important role of outdoor environment or synthetic environment as one of the factors that determine the patient’s recovery process in a hospital. Heart disease is one of the most deadliest ill with high risk of death in Indonesia after stroke. Patient’s stress factor are equals to the disease diagnosis which he/she suffered in and also patient,s recovery process factor are determined by environment factor for about 40%, 10% medical factor, 20% genetical factor and 30% for others factor. Seeing from this context, the writer conclude that environment has an important role on patienr’s recovery process with a type of disease with high stress-prone levels. To answer this as a solution, the writet apply and adapt a healing garden to its Cardiovascular Hospital design process at Tgk Daud Beureueh street number 108 Bandar Baru, Kuta Alam, Banda Aceh, Aceh. The application process will be explained with an introduction of healing garden, element and requirement for healing garden until reach a zoning section on Cardiovascular Hospital itself